Geochronology and Geochemistry of the Late Cretaceous Basalts in the Jiaolai Basin: Constraints on Lithospheric Thinning and Accretion Beneath North China Craton - Kuang, Y.; Pang, Chongjin; Hong, L.; Zhong, Y.; Xu, Y. (Zhongguo Kexueyuan Guangzhou Diqiu Huaxue Yanjiusuo, 2012)
Previous studies showed a heterogeneous temporal and spatial pattern of lithospheric thinning beneath North China Craton(NCC).The idea is mainly built on the diachronous eruption of the earliest asthenosphere-derived magmas in northern and southern NCC. In this study,we carried out Ar-Ar dating on the Xiguanzhuang tholeiitic basalt(the Jiaolai basin).40 Ar-39 Ar data show that it erupted at 96±3 Ma,thus belonging to the Qingshan Group,earlier than the Daxizhuang alkaline basalt(73 Ma) of the Wangshi Group. Both rocks show no negative Nb and Ta anomalies, but display E-MORB-like and OIB-like trace element distribution patterns, respectively. However, the Xiguanzhuang tholeiitic basalts have higher (87 Sr/86 Sr) and lower ε Nd(t)(0.7058,0.37～0.57) than the Daxizhuang alkaline basalts(0.7040,5.5～5.7). It is suggested that the former was formed as a result of interaction between asthenospheric melts and old-enriched lithosphere, whereas the latter represents asthenosphere-derived melts.The ε Nd(t) values in the studied magmas increase with decreasing age, consistent with upwelling of asthenosphere subsequent to the thinning of ancient lithosphere. This marks lithospheric thinning during Late Cretaceous-Early Cenozoic. Similar temporal variations in ε Nd(t) values are also observed for magmas in the western(120～100 Ma) and eastern(80～60 Ma) Liaoning province. This again attests to diachroneity of lithospheric thinning processes beneath the North China Craton.